FEATURES OF THE FORMATION OF ENVIRONMENTAL RESPONSIBILITY OF FUTURE MASTERS OF PRODUCTION TRAINING OF SEWING PROFILE IN THE EDUCATIONAL ENVIRONMENT OF THE VOCATIONAL COLLEGE (Innovative professional education, 2024)
The priority direction on the way to minimizing the negative impact of human activities on the environment is the introduction of global and personal environmental responsibility. The educational environment of the vocational college creates a powerful potential for the formation of environmental responsibility of future masters of production training of the sewing profile as a quality of personality that associates itself with nature, is an organic part of the environment and is able to positively influence it, change and change itself. The publication highlights the features and opportunities for the formation of appropriate quality in the process of studying educational components, carrying out extracurricular and educational activities.
Keywords: environmental responsibility, specialty college, educational environment, masters of industrial education, sewing profile